(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The anti-inflammatory, antibacterial effect, and anti-aging properties of the venom of honey bee Apis mellifera L. have been investigated and exploited for pharmaceutical and cosmetic applications for decades. Apitoxin, a drug based on bee venom, is administered via injection and is permitted for use in humans for its antipyretic, analgesic, and anti-inflammatory properties. This study was conducted to expand the scope of apitoxin application to arthritis. We used a DBA-1J mouse model of collagen-induced arthritis (CIA). Apitoxin was injected intradermally into the mice twice a week, and the body weight, arthritis score, and hindlimb paw edema were recorded once a week for 4 weeks in mice with CIA. The body weight of the groups with CIA was significantly lower than that of the group without CIA during the experimental period. Although the arthritis scores of all groups with CIA were higher than those of the group without CIA, the high dose apitoxin-treated group had a significantly improved arthritis score than the vehicle group on days 14 and 28. A significant reduction in edema was observed in the hindlimb paws in the apitoxin-treated group compared with that in the vehicle group. Additionally, inflammatory cytokines, such as IL-6 and IL-1β, and IgG antibodies to type II collagen, were detected in the articular tissue of mice with CIA on day 28. Both IL-6 and anti-type II collagen IgG levels significantly decreased in the apitoxin-treated group compared with those in the vehicle group. Histopathological analysis of the articular tissue also revealed similar improved results in the apitoxin-treated group. In conclusion, these results suggested that apitoxin has potential therapeutic application in patients with arthritis.